The Effectivity of Bacteria Isolated From of Liquid Waste Palm Oil Plantation on Ganoderma Boninense - Fitratul Aini (International Journal of Ecophysiology, 2019)
Ganoderma boninense is one of the main pathogenic fungus in oil palm plantations. Generally, these pathogen cause root rot (basal stem rot). Biological control that has been widely used reduce the infection is using bacteria. Liquid waste palm oil has potential to produce bacteria that is able to degrade Ganoderma boninense that causes root rot in oil palm. Liquid waste were obtained from Muaro Sabak Regency Jambi Province. Bacteri were isolated and cultivated in nutrient agar medium, characterized and identified for antagonistic test against G. boninense. Results showed that 16 bacterial isolates were identified, among of them are able to inhibit Ganoderma boninense.